2017
DOI: 10.5993/ajhb.41.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Use Linked to High-sugar Beverage Intake and BMI among Teens

Abstract: Adolescents who consume energy drinks during the past 7 days are more likely to also consume other high-sugar beverages. Whereas those who report no past 7-day use of energy drinks consume higher rates of low- or no-sugar beverages. Health education and prevention efforts to reduce adolescent energy drink consumption may lead to reductions in other high-sugar beverage intake and have a positive impact on obesity rates among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…For both sexes, adolescents who consumed HCB were more likely to be obese, to drink soda at least once a week, and to drink sweetened beverage at least once a week. This not only confirms previous findings that the sugar content and the subsequent sweet flavor are reasons why adolescent consume HCBs [36,37], but it also suggests that for adolescents consuming HCBs, the sugar content and its subsequent impact on weight may mask any weight-loss effect expected from the caffeine content [23,26].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For both sexes, adolescents who consumed HCB were more likely to be obese, to drink soda at least once a week, and to drink sweetened beverage at least once a week. This not only confirms previous findings that the sugar content and the subsequent sweet flavor are reasons why adolescent consume HCBs [36,37], but it also suggests that for adolescents consuming HCBs, the sugar content and its subsequent impact on weight may mask any weight-loss effect expected from the caffeine content [23,26].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have focused on sleep, stress, and psychological correlates of highly caffeinated beverage consumption among Korean adolescents [5,6]. Relatively less attention was given to factors that may influence individuals' decision to use HCB, such as nutrition [20,21], physical activity level [22], and body mass index (BMI) [23]. Few of the studies that considered such factors were not generalizable to the entire Korean adolescent population [21,24].…”
mentioning
confidence: 99%
“…Joint HCB consumption with substance use and other at-risk behaviours such as binge drinking, sweetened beverage intake, junk food, steroid and performance-enhancing substances intake or the number of hours playing video games is often reported in children and young adults. 32,42,46 HCB consumption has also been positively linked to body mass index (BMI), due to sugar contained in HCBs and the associated eating behaviours that promote obesity and diabetes. 35,46 However, BMI is difficult to interpret in rugby players, regarding the wide range of morphologies in amateur practicing and the specific impact of sport-related elevation in muscle mass on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…32,42,46 HCB consumption has also been positively linked to body mass index (BMI), due to sugar contained in HCBs and the associated eating behaviours that promote obesity and diabetes. 35,46 However, BMI is difficult to interpret in rugby players, regarding the wide range of morphologies in amateur practicing and the specific impact of sport-related elevation in muscle mass on BMI. Recent data has shown that measure of body composition using body fat mass index (BFMI) and fat-free mass index (FFMI) body BFMI are needed to avoid misclassifications in rugby players.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of sugar-sweetened beverages (SSB) such as sodas is linked to adverse health consequences including obesity [13] and various metabolic health impacts [4, 5] including dyslipidemia [6], diabetes [7], dental caries [8] and poor sleep hygiene [9, 10] . Artificially-sweetened beverages are also associated with higher energy intake despite their calorie-free properties [11], possibly due to their heightened sweetness which may impact one’s perception of energy intake [12].…”
Section: Introductionmentioning
confidence: 99%